PENEGAKAN HUKUM TINDAK PIDANA PENCURIAN DENGAN MODUS PROSTITUSI MELALUI APLIKASI MICHAT OLEH KEPOLISIAN (STUDI PADA POLSEK MEDAN KOTA) - Sher Muhammad Anwar; Wessy Trisna; Abdul Aziz Alsa (Smart Education, 2025)
Abstract: This study aims to analyze law enforcement against the crime of theft with the mode of prostitution carried out through the MiChat application, focusing on the Medan City Police. This crime utilizes digital technology, where the perpetrator uses the